On the Prevalence of Addicted or Problematic Gaming in Finland - Veli-Matti Karhulahti; Raine Koskimaa (My University, 2022)
We bring attention to a notable unreported “gaming addiction” or “problem gaming” prevalence data set that adds significantly to both the DSM-5′s call for further Internet Gaming Disorder research as well as many other scientific encouragements for more wide-ranging reports on the topic.